Molecular Functionalization of Chemically Active Defects in WSe2 for Enhanced Opto‐Electronics. (6th September 2020) - Zhao, Yuda; Gali, Sai Manoj; Wang, Can; Pershin, Anton; Slassi, Amine; Beljonne, David; Samorì, Paolo
Abstract: Structural defects are known to worsen electrical and optical properties of 2D materials. Transition metal dichalcogenides (TMDs) are prone to chalcogen vacancies and molecular functionalization of these vacancies offers a powerful strategy to engineer the crystal structure by healing such defects. This molecular approach can effectively improve physical properties of 2D materials and optimize the performance of 2D electronic devices. While this strategy has been successfully exploited to heal vacancies in sulfides, its viability on selenides based TMDs has not yet been proven. Here, by using thiophenol molecules to functionalize monolayer WSe2 surface containing Se vacancies, it is demonstrated that the defect healing via molecular approach not only improves the performance of WSe2 transistors (> tenfold increase in the current density, the electron mobility, and the I on / I off ratio), but also enhances the photoluminescence properties of monolayer WSe2 flakes (threefold increase of photoluminescence intensity at room temperature). Theoretical calculations elucidate the mechanism of molecular passivation, which originates from the strong interaction between thiol functional group at Se vacancy sites and neighboring tungsten atoms. These results demonstrate that the molecular approach represents a powerful strategy to engineer WSe2 transistors and optimize their optical properties, paving the way toward high‐performance 2D (opto)electronic devices. Abstract : The defect passivation of monolayer WSe2 by thiophenol molecules is investigated. The direct observation of thiophenol adsorbed on Se vacancy sites by STM, the improved electrical transport properties in transistors, and the enhanced photoluminescence intensity provide strong evidence for the vacancy healing via molecular functionalization. These findings provide a viable approach to engineer defects in transition metal diselenides.